Ethanol-Induced Alterations of T Cells and Cytokines after Surgery in a Murine Infection Model - Nadine Lanzke; Mario Menk; Clarissa von Haefen; Lilit Sargsyan; Bianca Scharf; Klaus-Dieter Wernecke; Claudia D. Spies (Hindawi Limited, 2017)
Background. Interactions between alcohol, infection, and surgery and their effect on differentiation and functionality of T helper cells are not yet completely understood. We hypothesized that alcohol and surgery disturb differentiation of T helper cells and contribute to an impaired immune response. Methods. Mice were treated with alcohol for two weeks. Saline treatment served as control. Clinical performance and weight were assessed. On day 14, a median laparotomy was performed and animals were challenged with Klebsiella pneumoniae intranasally. Bacterial load was determined in lungs and blood. T helper cell subpopulations and the released cytokines were assessed in lungs, spleens, and plasma. Key transcription factors of T cell differentiation were evaluated. Results. Alcohol significantly impaired clinical appearance and body weight of animals with postsurgical infection (p<0.05). Bacterial load was significantly higher after alcohol treatment (p<0.05). T helper cell subsets and released cytokine levels were significantly altered in lung, but not in spleen. Expression of transcription factors of T helper cell lineage commitment did not translate into different counts of T helper cells. Conclusions. Alcohol and surgery lead to significant cellular and functional modulations of T helper cells during postsurgical infection. These effects may contribute to an impaired immune response after surgery.